2015
DOI: 10.1038/srep08484
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic population screen identifies a new mutation in bovine DGAT1 responsible for unsaturated milk fat

Abstract: Selective breeding has strongly reduced the genetic diversity in livestock species, and contemporary breeding practices exclude potentially beneficial rare genetic variation from the future gene pool. Here we test whether important traits arising by new mutations can be identified and rescued in highly selected populations. We screened milks from 2.5 million cows to identify an exceptional individual which produced milk with reduced saturated fat content, and improved unsaturated and omega-3 fatty acid concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 36 publications
3
19
0
Order By: Relevance
“…While it is not the first time an expression-based effect of DGAT1 has been proposed as the mechanism by which this gene influences milk composition [14], our study is the first to provide evidence supporting an expression-based effect associated with K232A. Association mapping at the DGAT1 locus using imputed WGS variants showed that DGAT1 K232A retains its status as one of the top ranking variants.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…While it is not the first time an expression-based effect of DGAT1 has been proposed as the mechanism by which this gene influences milk composition [14], our study is the first to provide evidence supporting an expression-based effect associated with K232A. Association mapping at the DGAT1 locus using imputed WGS variants showed that DGAT1 K232A retains its status as one of the top ranking variants.…”
Section: Discussionsupporting
confidence: 48%
“…Additionally, the disruption of splicing has recently been reported for a novel DGAT1 mutation in dairy cattle, whereby a non-synonymous A>C transversion in exon 16 disrupts a putative ESE motif and causes the skipping of this exon [14]. This polymorphism results in an enzymatically inactive DGAT1, which in the homozygous state results in a severe phenotype characterised by scouring and slow growth [14].…”
Section: Discussionmentioning
confidence: 99%
“…18,19 However, in humans only a single family has been reported associated with DGAT1 mutations. Haas et al described a non-consanguineous AshkenaziJewish family in which two of three siblings were homozygous for a splice site mutation leading to exon 8 deletion associated with PLE, hypoalbuminemia, and early-onset diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…Development of Saanen goat breeding can not be separated from the selection process of livestock. Conventional selection based on ancestral performance takes a lot of time, so genetic markers underlying commercial phenotype trait as selection mechanism, or known as Marker-Assisted Selection (MAS) was used to abbreviate time and enhance the accurate of selection Lehnert et al, 2015;Muhammed et al, 2015).…”
Section: Introductionmentioning
confidence: 99%